Flying tigers [videorecording (DVD)] - Miller, David, 1909-1992; Wayne, John, 1907-1979; Carroll, John, 1906-1979; Lee, Anna, 1913-2004 (Republic Entertainment Inc. ; Distributed by Artisan Home Entertainment, 2000)
Heroic story of American airmen fighting the Japanese over China in early World War II.